Lifestyles of Jerusalem’s Rich and Famous - Gadot, Yuval 1967-; Shalev, Yiftah 19XX- (2024)
The Iron Age building recently excavated in the Givati Parking Lot section of the City of David was unique in Jerusalem’s ancient landscape. A magnificent residence and reception hall used for official ceremonies and social gatherings, it may be identified with the biblical "chamber," reflecting the daily life of Jerusalem’s ruling elite at the end of the First Temple period.